1997
DOI: 10.4315/0362-028x-60.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of Organic Acids against Salmonella typhimurium Attached to Broiler Chicken Skint

Abstract: The bactericidal activity of 0.5, 1,2,4, and 6% acetic, citric, lactic, malic, mandelic, propionic, or tartaric acid was determined against Salmonella typhimurium that were loosely or firmly attached to broiler chicken skin by using the skin-attachment model. Acid treatments were applied during a simulated chill (0°C/60 min), postprocess dip (23°C for 15 s), or scald (50°C for 2 min). For comparison, activity of the acid treatments when applied under these conditions were also determined against S. typhimurium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 0 publications
6
59
0
9
Order By: Relevance
“…However, in comparison to the reduction of the initial contamination observed on breast muscles (20-fold) after application of lysozyme with the activity of 12,000 U/mL, it may be concluded that the surface of the skin (higher pH, considerable undulation) is more prone to the development of microorganisms, as it exhibits increased adhesiveness and forms a protective layer for microorganisms (13). Similar conclusions concerning microbiological contamination revealed on poultry skin may be also found in other publications (6,19,29). In the previous experiment on chicken breasts, an effective limitation of bacterial growth during cold storage of samples was already demonstrated at the enzyme activity of 6,000 U/mL (13).…”
Section: Discussionsupporting
confidence: 87%
“…However, in comparison to the reduction of the initial contamination observed on breast muscles (20-fold) after application of lysozyme with the activity of 12,000 U/mL, it may be concluded that the surface of the skin (higher pH, considerable undulation) is more prone to the development of microorganisms, as it exhibits increased adhesiveness and forms a protective layer for microorganisms (13). Similar conclusions concerning microbiological contamination revealed on poultry skin may be also found in other publications (6,19,29). In the previous experiment on chicken breasts, an effective limitation of bacterial growth during cold storage of samples was already demonstrated at the enzyme activity of 6,000 U/mL (13).…”
Section: Discussionsupporting
confidence: 87%
“…These acids are generally weak antimicrobial agents and are less effective for surface decontamination. A study reported by Tamblyn and Conner (1997) in which they treated chicken breast meat with 0.5 and 1 % malic acid stored at 4°C for 60 min and recorded 1.2 to 2.16 log reduction of S. typhimurium, respectively. They further applied malic acid under scalded conditions at 50°C for 2 min and found 1.62 logs reduction of microorganism.…”
Section: Organic Acids As Antimicrobial Agentmentioning
confidence: 97%
“…If intracellular pH is higher than acid dissociation constant (pKa), the acid may disassociate by releasing a proton, and by this way to acidify the cytoplasm of the microorganism (Booth 1985). The antibacterial effect of lactic acid varies depending on the concentration, temperature and the method of application (Tamblyn and Conner 1997). The effect of lactic acid on meat quality and sensory properties has been studied in different species such as cattle, chicken, buffalo and pig (Jimenez-Villareal et al 2003ab, Kotula and Thelappurath 1994, Pipek et al 2005, Deumier 2004, Surve et al 1991, Van Netten et al1995, Jensen et al 2003.…”
Section: Introductionmentioning
confidence: 99%